2017
DOI: 10.1177/000313481708300528
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection Rate Drops to 0% Using a Vacuum-Assisted Closure in Contaminated/ Dirty Infected Laparotomy Wounds

Abstract: Wound site infections increase costs, hospital stay, morbidity, and mortality. Techniques used for wounds management after laparotomy are primary, delayed primary, and vacuum-assisted closures. The objective of this study is to compare infection rates between those techniques in contaminated and dirty/ infected wounds. Eighty-one laparotomized patients with Class III or IV surgical wounds were enrolled in a three-arm randomized prospective study. Patients were allocated to each group with the software Research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…Other studies [13,14] concluded that the biological interaction between the foam and the wound base has similarities with a nonspecific foreign body-like reaction and results from yet unknown pathways. Recent studies [15,16] brought more light to the matter. https://doi.org/10.37358/MP.20.2.5348…”
Section: Resultsmentioning
confidence: 99%
“…Other studies [13,14] concluded that the biological interaction between the foam and the wound base has similarities with a nonspecific foreign body-like reaction and results from yet unknown pathways. Recent studies [15,16] brought more light to the matter. https://doi.org/10.37358/MP.20.2.5348…”
Section: Resultsmentioning
confidence: 99%
“…A total of 35 articles discussed prophylactic VSD (pVSD) for abdominal incisions with primary suture, of which 6 were RCTs 32 , 33 , 34 , 35 , 36 , 37 and 29 were observational studies. 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 …”
Section: Recommendationsmentioning
confidence: 99%
“… 34 Eleven observational studies of abdominal surgeries, including pediatric contaminated surgery, gynecological malignancy surgery, cesarean section surgery, and liver transplantation surgery, also showed that pVSD reduced the incidence of incision infections. 44 , 45 , 49 , 50 , 52 , 57 , 59 , 65 One RCT showed that pVSD reduced postoperative pain and the need for anesthetics 34 ; however, although the incidence of SSIs decreased, the difference was not significant.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technology may intermittently or continuously generate a pressure lower than atmospheric pressure at the wound surface and promote wound healing through a series of physiological mechanisms ( 8 ). VSD may be applied to various types of wounds, including infected wounds, skin graft wounds and wounds without skin or soft tissue ( 9 , 10 ). This technique has outstanding advantages in clinical application, e.g.…”
Section: Introductionmentioning
confidence: 99%